2013
DOI: 10.1371/journal.ppat.1003564
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Calcineurin at a Novel Serine-Proline Rich Region Orchestrates Hyphal Growth and Virulence in Aspergillus fumigatus

Abstract: The fungus Aspergillus fumigatus is a leading infectious killer in immunocompromised patients. Calcineurin, a calmodulin (CaM)-dependent protein phosphatase comprised of calcineurin A (CnaA) and calcineurin B (CnaB) subunits, localizes at the hyphal tips and septa to direct A. fumigatus invasion and virulence. Here we identified a novel serine-proline rich region (SPRR) located between two conserved CnaA domains, the CnaB-binding helix and the CaM-binding domain, that is evolutionarily conserved and unique to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 50 publications
0
56
0
1
Order By: Relevance
“…Thus, research on the differences between the calcineurins of fungal and mammalian cells is urgently needed to develop antifungal-specific drugs. Fortunately, Juvvadi et al (119) have found a novel serineproline-rich region (SPRR) that is evolutionarily conserved and unique to filamentous fungi but completely absent in human calcineurin. The SPRR appears to be required for the phosphorylation of calcineurin that enables it to be active and function well.…”
Section: Interference With Calcineurinmentioning
confidence: 99%
“…Thus, research on the differences between the calcineurins of fungal and mammalian cells is urgently needed to develop antifungal-specific drugs. Fortunately, Juvvadi et al (119) have found a novel serineproline-rich region (SPRR) that is evolutionarily conserved and unique to filamentous fungi but completely absent in human calcineurin. The SPRR appears to be required for the phosphorylation of calcineurin that enables it to be active and function well.…”
Section: Interference With Calcineurinmentioning
confidence: 99%
“…But as Crz1 and its orthologues are restricted to lower eukaryotes and cannot be found in higher eukaryotes (see below), it might be worth investigating this class of transcription factors in more detail to find structures that are common in those proteins and that could serve as potential drug targets. Such a strategy was successfully followed in investigating calcineurin of A. fumigatus (77). Calcineurin of A. fumigatus harbors a novel serine-proline-rich region that is conserved, unique to filamentous fungi, and completely absent in human calcineurin.…”
Section: Crz1 As a Drug Target?mentioning
confidence: 99%
“…Calcineurin of A. fumigatus harbors a novel serine-proline-rich region that is conserved, unique to filamentous fungi, and completely absent in human calcineurin. This offers the potential to design a specific drug targeting this region (77).…”
Section: Crz1 As a Drug Target?mentioning
confidence: 99%
“…85,92 Although mutations in functional domains of calcineurin have revealed important residues required for localization and function of calcineurin at the septum, the exact mechanism of how calcineurin regulates septation is still unclear. 93,94 A filamentous fungalspecific serine proline rich (SPRR) linker domain between the CnBBH and CaMBD was also identified in the A. fumigatus calcineurin catalytic subunit. 93 This SPRR was phosphorylated at all 4 clustered serine residues and mutations in this region caused hyphal growth and virulence defects, implicating the importance of calcineurin phosphorylation for its function.…”
Section: Aspergillus Fumigatusmentioning
confidence: 99%
“…93,94 A filamentous fungalspecific serine proline rich (SPRR) linker domain between the CnBBH and CaMBD was also identified in the A. fumigatus calcineurin catalytic subunit. 93 This SPRR was phosphorylated at all 4 clustered serine residues and mutations in this region caused hyphal growth and virulence defects, implicating the importance of calcineurin phosphorylation for its function. 93 Identification of key regions for calcineurin function that are unique to fungi and absent in humans is a promising step toward the development of novel antifungal therapies.…”
Section: Aspergillus Fumigatusmentioning
confidence: 99%